AstraZeneca and Covance Laboratories Clinical Bioanalysis Alliance: an evolutionary outsourcing model. (August 2017) - Arfvidsson, Cecilia; Severin, Paul; Holmes, Victoria; Mitchell, Richard; Bailey, Christopher; Cape, Stephanie; Li, Yan; Harter, Tammy
The AstraZeneca and Covance Laboratories Clinical Bioanalysis Alliance (CBioA) was launched in 2011 after a period of global economic recession. In this challenging environment, AstraZeneca elected to move to a full and centralized outsourcing model that could optimize the number of people supporting bioanalytical work and reduce the analytical cost. This paper describes the key aspects of CBioA, the innovative operational model implemented, and our ways of ensuring this was much more than simply a cost reduction exercise. As we have recently passed the first 5-year cycle, this paper also summarizes some of the concluding benefits, wins and lessons learned, and how we now plan to extend and develop the relationship even further moving into a new clinical laboratory partnership.